Special issue : law and the imagining of difference - Sarat, Austin (Emerald Publishing, 2018)
This volume focusses on Law and the Imagining of Difference with each chapter examining how law responds to the claims of difference, how and when it recognizes difference and accommodates it, as well as when and why such recognition and accommodation is resisted. Topics covered include disability, same-sex marriage and gender equality.
Keywords: Cultural pluralism.; Equality.; Cultural Diversity; Diversité culturelle.; Law & society.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Cultural pluralism; Equality